RELATIONSHIP BETWEEN BANKING SERVICE AND SETTLEMENT WITH MENTAL HEALTH OF XI CLASS 1 DUAPITUE STATE HIGH SCHOOL, SIDENRENG DISTRICT, RAPPANG - Mukhtar Saleh (Celebes Education Review, 2019)
The purpose of this study was to determine the relationship between Guidance and Counseling Services with Class XI Mental Health of Duapitue 1 High School in Sidenreng Rappang District. This study uses a pre-experimental method. The population of this study is the XI grade 1 SMA 1 Sidrap academic year 2018/2019. The sample is 20 students. Sampling uses purposive sampling in one class. It was found that there was a significant relationship between pre-test and post-test of student achievement in counseling services. Therefore, it can be concluded that there is a relationship between counseling services and mental health of Grade IX students of SMAN1 Sidrap.